Theatre Involvement and Well-Being, Age Differences, and Lessons From Long-Time Subscribers. (8th April 2017) - Meeks, Suzanne; Shryock, Sarah Kelly; Vandenbroucke, Russell J
Abstract: Background and Objectives: Activities that provide positive emotions, meaningful social interaction, and psychological stimulation can bolster well-being throughout life. We tested a model of psychological benefit from, and age differences in, adult ticket buyers' involvement with a large regional theatre. Research Design and Methods: We sent online surveys to Actors Theatre of Louisville ticketbuyers, measuring involvement with the theatre, satisfaction/enjoyment, social engagement, flow, and sense of belonging while attending, and well-being. Structural models ( N = 496) tested a model of well-being and age differences; focus groups of older subscribers ( N = 20) elaborated quantitative findings. Results: As hypothesized, theatre involvement was indirectly related to satisfaction and enjoyment of the theatre, hedonic well-being, and social functioning, through the psychosocial benefits of flow, social engagement, and belonging. Age moderated the model relationships: involvement was more strongly related to benefits for younger than older participants, but there were no age differences in the relationship between benefits and well-being. Focus group participants articulated how theatre contributes to a sense of community and pride of place, connecting individual well-being to community well-being. Discussion and Implications: Involvement in performing arts organizations may have lifelong benefits. The relationship between involvement and psychosocial benefit may be particularly strong for younger audience members despite the fact that older adults have more involvement. Older adults with long-term involvement appear to benefit even when they reduce their involvement. Our qualitative findings underscore the great richness of experience that younger generations might lose as a result of lower participation.